Effects of dapagliflozin on serum uric acid levels in hospitalized type 2 diabetic patients with inadequate glycemic control: a randomized controlled trial - Hao Z; Huang X; Shao H; Tian F (Dove Medical Press, 2018)
Zhaohu Hao,1,* Xiao Huang,2,* Hailin Shao,1 Fengshi Tian1,3 1Department of Metabolic Disease Management Center, Tianjin 4th Central Hospital, Tianjin, China; 2NHC Key Laboratory of Hormones and Development (Tianjin Medical University), Tianjin Key Laboratory of Metabolic Diseases, Tianjin Medical University Metabolic Diseases Hospital and Tianjin Institute of Endocrinology, Tianjin Medical University, Tianjin, China; 3Department of Cardiology, Tianjin 4th Central Hospital, The 4th Central Hospital Affiliated to Nankai University, The 4th Center Clinical College of Tianjin Medical University, Tianjin, China *These authors contributed equally to this work Background: Raised serum uric acid (SUA) level is commonly observed in patients with type 2 diabetes mellitus (T2DM) and is associated with increased morbidity and mortality. Sodium-glucose cotransporter 2 inhibitor, a novel oral diabetic drug, might exert a potential hypouricemic effect. We evaluated the effects of dapagliflozin on SUA levels in hospitalized T2DM patients with inadequate glycemic control. Methods: In this randomized controlled trial, 59 T2DM hospitalized patients with inadequate glycemic control were assigned to the dapagliflozin 10 mg group (n=29) or the control group (n=30). The primary outcome was changes in SUA levels from the baseline to good glycemic control. Additional outcomes included correlations between baseline SUA levels, urinary parameters, and the changes in SUA levels. This trial is registered in the Chinese Clinical Trial Registry (number ChiCTR1800015830). Results: Compared to baseline level, SUA levels had significantly decreased in both groups (P<0.001 for the dapagliflozin group and P=0.013 for the control group). Mean changes from baseline in SUA levels for dapagliflozin vs the control group were 68.03 vs 25.90 µmol/L (P=0.0406). Adjusted mean SUA levels were lower in the dapagliflozin group (273.28 vs 307.57 µmol/L; P=0.0089). In T2DM patients treated with dapagliflozin, the decrease in SUA levels was positively correlated with baseline SUA levels (P<0.0001) but not correlated with changes in 24-hour urine volume, 24-hour urine glucose, or 24-hour urinary uric acid. Conclusion: Dapagliflozin could improve glycemic control and lower SUA levels in hospitalized patients with uncontrolled T2DM. Longer-time trials are required to further demonstrate the hypouricemic effect of dapagliflozin and explore the potential underlying mechanisms. Keywords: serum uric acid, dapagliflozin, type 2 diabetes mellitus, 24-hour urinary uric acid, SGLT2 inhibitor